2021
DOI: 10.3390/nano11020264
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Hydroxyapatite Derived from Biogenic and Bioinspired Calcium Carbonates: Synthesis and In Vitro Bioactivity

Abstract: Biogenic calcium carbonates naturally contain ions that can be beneficial for bone regeneration and therefore are attractive resources for the production of bioactive calcium phosphates. In the present work, cuttlefish bones, mussel shells, chicken eggshells and bioinspired amorphous calcium carbonate were used to synthesize hydroxyapatite nano-powders which were consolidated into cylindrical pellets by uniaxial pressing and sintering 800–1100 °C. Mineralogical, structural and chemical composition were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 77 publications
1
45
0
Order By: Relevance
“…The XRD pattern in Figure 1 was matched by the calcite (CaCO 3 ) phase with a high degree of crystallinity evidenced by sharp diffraction peaks. The results are in good agreement with numerous references, which present egg-shells as a calcium carbonate source [ 24 , 25 ]. In addition, a calcium content of 96.38 wt.% was observed after XRF examination, made on egg-shells before calcination.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The XRD pattern in Figure 1 was matched by the calcite (CaCO 3 ) phase with a high degree of crystallinity evidenced by sharp diffraction peaks. The results are in good agreement with numerous references, which present egg-shells as a calcium carbonate source [ 24 , 25 ]. In addition, a calcium content of 96.38 wt.% was observed after XRF examination, made on egg-shells before calcination.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, natural sources for biological apatite synthesis have been extended, year by year, from mammalian bone sources next to fish bones and scales [ 20 , 21 , 22 ], egg-shells [ 23 , 24 ], and exoskeletons of marine organisms (snails, starfish, coral, and seashell) [ 25 , 26 , 27 , 28 ] or botanic sources (Calendula flower, Papaya leaf, and orange peel), where all of them need chemical and thermal preparation before use as a mammalian xenograft. However, the interest in this topic is still present, a fact proved by several recent publications [ 23 , 24 , 25 ]. Mammalian bone, after thermal treatments, provides so-called biological apatite [ 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]; egg-shells (hen, crocodile etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been widely used for the removal of heavy metals [ 15 , 16 ] and arsenic from wastewater [ 17 ]. Regarding the importance of Hap, day by day researchers are exploring their focus on developing various synthetic routes using either chemical sources or biogenic resources/ bio-wastes [ 10 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%